Work measurement - Bollinger, Steven R.; Pardee, Clark; Society of Manufacturing Engineers ([Dearborn, MI] : The Society, 1997)
Explains current practices in work measurement and shows how manufacturers use this procedure to measure productivity improvements. Visits Cooper Instrument Corporation, MacGregor Golf, Cramerton Automotive Products, and Kohler factories. Includes interviews with experts Royal Dossett and Donovan Young.
Fakulti Teknologi Kreatif Dan Warisan.
Keywords: Production engineering; Time study; Work measurement